PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS DENGAN KINERJA LINGKUNGAN SEBAGAI VARIABEL MEDIASI - Vidya Artika Kurniawati Kurniawati; Susi Handayani (Media Mahardhika, 2026)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on profitability, with environmental performance as a mediating variable, in the manufacturing sector during the 2021-2024 period. The research method employed a quantitative approach, using multiple linear regression analysis and the Sobel test to examine the mediating role. The results indicate that CSR disclosure has no effect on corporate profitability. However, CSR disclosure has a significant effect on environmental performance. Conversely, environmental performance was found to have no effect on profitability, and environmental performance was unable to mediate the relationship between CSR disclosure and corporate profitability. This study contributes to understanding the relationship between CSR and profitability, providing perspective that other factors beyond the research model influence corporate profitability. Keywords: Corporate Social Responsibility, Profitability, Environmental Performance, Global Reporting Initiative, Return On Asset, PROPER.